Analisis Kesalahan Sintaksis pada Teks Makalah dalam Modul Ajar Kelas 10 Kurikulum Merdeka - Nilam Nathania; Hidayatun Toyibah Priyati Istu Utami; Aulia Rizky Nur Ruwita; Fiki Nushrotul Hafidh; Asep Purwo Yudi Utomo; Fahrudin Eko Hardiyanto (Student Scientific Creativity Journal, 2023)
A quality paper is a good and correct paper the writing code, the synthesis of it, and the aspects of its meaning. However, incorrect papers on writing are often found. It would be necessary to analyze the syntax error on the paper to identify any of the existing syntax errors and to provide the corresponding explanation. The approach researchers use is a methodological approach and a theoretical approach. The methodological approach that researchers use is a descriptive qualitative approach, while the theoretical approach is a syntax approach. A descriptive qualitative approach by gathering data, identifying, analyzing data, and defining analysis results. The syntax approach by reading, analyzing, analyzing, and noting the results of syntax analysis. These two approaches are what researchers use in analyzing syntax errors in the paper. The object of the study that researchers are using is a paper entitled the Theory of Learning and Learning. Research in this article shows that the KBBI and EYD codes still vary in number. Not only that, there was also cohesion, cohesive, and the squandering of words that resulted in inadequate discourse. The study is done to find out what makes it unqualified and to explain detailed analysis results.